The methodology of strategic management of food industry enterprises against the background of the tasks of ensuring food security of Ukraine - Klius, V. (Global Prosperity, 2022)
Klius V. The methodology of strategic management of food industry enterprises against the background of the tasks of ensuring food security of Ukraine. Global Prosperity. 2022. Vol. 2. Issue 4